DRUG UTILIZATION STUDY IN POST-OPERATIVE PATIENTS IN THE SURGERY WARD OF A TERTIARY CARE TEACHING HOSPITAL IN SOUTH INDIA - Arshad, Mohammad; M, Raghunandan; Chavan, Vasant R; Fayazuddin, Mohd (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Pharmacotherapy with multiple agents before, during, and after surgery is marked in the present day indoor hospital setting. The main objective of our research is to evaluate the prescribing and drug utilization patterns using the World Health Organization (WHO) indicators in post-operative patients in the surgery ward of Raichur Institute of Medical Sciences (RIMS) teaching hospital - Raichur, which will help us to use the medicines rationally and decrease the adverse effects in surgical patients. Methods: A retrospective study was done on post-operative patients of surgery ward in RIMS teaching hospital - Raichur. A total of 574 patients prescriptions/case record forms were collected over a period of 15 months from January 2015 to March 2016 from the medical record section of the hospital for analysis and rationalization. We analyzed the data using the various drug use indicators given by the WHO. Results: The average number of drugs per encounter was 7.04. Ranitidine, analgesics, antibiotics, and intravenous fluids accounted for majority of the drugs prescribed. Appendicectomy (34.84%) was most commonly performed surgical procedure. Percentage of encounters in which an antibiotic prescribed was 99.8%. Percentage of encounters with an injection prescribed was 100%. Percentage of drugs prescribed by generic name was 43.93%. Percentage of drugs prescribed from National List of Essential Medicines 2015 was 99.3%. Conclusion: Our study gave us an in general pattern about the use of drugs in post-operative patients in the surgical ward of a tertiary care hospital. Widespread polypharmacy, particularly in case of the antibiotics, lack of generic prescribing are some concerns that need to be addressed to conform to rational drug therapy. However, prescribing according to the national essential list of medicines is good in our study.